Zui hou de zhan xiang da bing lin wang - Li, Ruqing 1962- (Pace Books, 2022)
Amei the elephant, born in the forest of Myanmar, was used as a transport elephant by the Japanese army that occupied Myanmar. After the Japanese army was defeated, the expeditionary army took over the elephants and Amei was used to build the Yunnan-Myanmar highway.